x is a positive integer which follows the condition 1 3 ∣ ( 4 x 2 − 2 2 x + 1 5 )
y is a positive integer which follows the condition 1 3 ∣ ( 4 y 2 + 2 2 y + 1 5 )
Let the sum of the first 2 5 smallest possible values of x be X .
Let the sum of the first 2 5 smallest possible values of y be Y .
Find the value of X + Y
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
4 x 2 − 2 2 x + 1 5 ≡ 0 ( m o d 1 3 ) ⟹ 4 x 2 − 9 x + 2 ≡ 0 ( m o d 1 3 ) Compare the expression 4 x 2 − 9 x + 2 with a x 2 + b x + c .
The solutions of this will be when we use the substitution
y = 2 a x + b and d = b 2 − 4 a c ,
and the solutions will be given by y 2 ≡ d ( m o d 1 3 )
Thus we get ( 8 x − 9 ) 2 ≡ 9 2 − 4 × 4 × 2 ≡ 4 9 ( m o d 1 3 )
This gives 8 x − 9 ≡ ± 7 ( m o d 1 3 ) . 8 x ≡ 1 6 or 2 ( m o d 1 3 )
This gives x ≡ 2 ( m o d 1 3 ) and other solution 4 x ≡ 1 ( m o d 1 3 ) ⟹ x ≡ − 3 ≡ 1 0 ( m o d 1 3 ) .
Thus x ≡ 2 or 1 0 ( m o d 1 3 )
Similarly solving for y , we get y ≡ 3 or 1 1 ( m o d 1 3 )
values of x are of the form 1 3 k + 2 and 1 3 k + 1 0
values of y are of the form 1 3 k + 3 and 1 3 k + 1 1
See that they are actually 4 A.P.s (Arithmetic Progressions) with common difference 1 3 .
The sum of first 2 5 values of x will be X = k = 0 ∑ 1 2 ( 2 + 1 3 k ) + k = 0 ∑ 1 1 ( 1 0 + 1 3 k )
The sum of first 2 5 values of y will be Y = k = 0 ∑ 1 2 ( 3 + 1 3 k ) + k = 0 ∑ 1 1 ( 1 1 + 1 3 k )
This gives X + Y = 4 0 6 1
Problem Loading...
Note Loading...
Set Loading...
4 x 2 − 2 2 x + 1 5 ≡ 0 ( m o d 1 3 ) ⟹ 4 x 2 + 4 x 2 + 2 ≡ 0 ( m o d 1 3 ) ( 2 x + 1 ) 2 ≡ 1 2 ( m o d 1 3 ) similarly 4 y 2 + 2 2 y + 1 5 ≡ 0 ( m o d 1 3 ) ⟹ ( 2 y − 1 ) 2 ≡ 1 2 ( m o d 1 3 ) let the 25 x A = x 1 , x 2 , x 3 , . . . . , x 2 5 .let the 25 y be B = x 1 + 1 , x 2 + 1 , x 3 + 1 , . . . . . , x 2 5 + 1 . note that if n 2 ≡ 1 2 ( m o d 1 3 ) , n ≡ 5 , 8 ( m o d 1 3 ) but since n has to be odd, for some integer z : 2 x + 1 = 1 3 ( 2 z ) + 5 , 1 3 ( 2 z + 1 ) + 8 2 x + 1 = 2 6 z + 5 , , 2 6 z + 2 1 x = 1 3 z + 2 , 1 3 z + 1 0 so X = n = 1 ∑ 2 5 ( x n ) = n = 0 ∑ 1 2 ( 1 3 n + 2 ) + n = 0 ∑ 1 1 ( 1 3 n + 1 0 ) X = 2 0 1 8 and Y = n = 1 ∑ 2 5 ( x n + 1 ) = X + 2 5 = 2 0 4 3 X + Y = 4 0 6 1